CORRELATION STUDIES BETWEEN FLORAL BIOLOGY AND FRUIT QUALITY IN DIFFERENT GENOTYPES OF APPLE COLOUR GUAVA (PSIDIUM GUAJAVA L.) - T. ANUPA; S. JAGANATH; PRAVEEN KUMAR ANGADI (The Bioscan, 2015)
Study of floral biology and developmental changes in fruits of Apple Colour guava (Psidium guajava L.)was carried out at Department of Horticulture, University of Agricultural Sciences, GKVK, Bengaluru during the year 2010-11on ten year old plants with the objective to study the correlation between the floral biology and fruit quality. Correlation studies of different characters in Apple Colour guava have revealed that the duration of flowering is positively and significantly correlated with total sugars (0.58*) and reducing sugars (0.73*) whereas, it is associated negatively significant with Titratable acidity (-0.83**) and pH (-0.83**) number of flowers per shoot was positively and significantly correlated with fruit retention (0.59*) and negatively significant associated with pH(-0.83**) fruit set is highly significant and positively correlated with fruit retention (0.98**) whereas negatively associated with pH (0.66*). The positive or negative correlation of different flowering and fruit quality parameters helps to understand the relationship between different apple colour guava genotypes.